Needs-based off-job crafting across different life domains and contexts: Testing a novel conceptual and measurement approach - Kujanpää, Miika; Syrek, Christine; Tay, Louis; Kinnunen, Ulla; Mäkikangas, Anne; Shimazu, Akihito; Wiese, Christopher W.; Brauchli, Rebecca; Bauer, Georg F.; Kerksieck, Philipp; Toyama, Hiroyuki; de Bloom, Jessica (Frontiers in Psychology, 2022)
Shaping off-job life is becoming increasingly important for workers to increase and maintain their optimal functioning (i.e., feeling and performing well). Proactively shaping the job domain (referred to as job crafting) has been extensively studied, but crafting in the off-job domain has received markedly less research attention. Based on the Integrative Needs Model of Crafting, needs-based off-job crafting is defined as workers’ proactive and self-initiated changes in their off-job lives, which target psychological needs satisfaction. Off-job crafting is posited as a possible means for workers to fulfill their needs and enhance well-being and performance over time. We developed a new scale to measure off-job crafting and examined its relationships to optimal functioning in different work contexts in different regions around the world (the United States, Germany, Austria, Switzerland, Finland, Japan, and the United Kingdom). Furthermore, we examined the criterion, convergent, incremental, discriminant, and structural validity evidence of the Needs-based Off-job Crafting Scale using multiple methods (longitudinal and cross-sectional survey studies, an “example generation”-task). The results showed that off-job crafting was related to optimal functioning over time, especially in the off-job domain but also in the job domain. Moreover, the novel off-job crafting scale had good convergent and discriminant validity, internal consistency, and test–retest reliability. To conclude, our series of studies in various countries show that off-job crafting can enhance optimal functioning in different life domains and support people in performing their duties sustainably. Therefore, shaping off-job life may be beneficial in an intensified and continually changing and challenging working life.